2015
DOI: 10.3109/09553002.2015.1028596
|View full text |Cite
|
Sign up to set email alerts
|

Effect of radiation on the nutritional and microbial qualities of salted and sun-dried Sharpfin barracuda (Sphyraena acutipinnis)

Abstract: The irradiation helps to improve the quality and safety of sun-dried fishes. The process would not only reduce the risk resulting from pathogens but also would destroy many of the spoilage agents like bacteria, insects, parasites, moulds and yeasts which are known to be the main cause of food losses in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Free amino acids are generally used as quality indices in various fish and crustacean species and are responsible for flavour and taste (Li et al, 2017). For example, alanine and glycine have a sweet taste, and glutamic acid has an umami taste (Prakash et al, 2015). Mo et al (2016) reported that the supplementation of (Lee et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Free amino acids are generally used as quality indices in various fish and crustacean species and are responsible for flavour and taste (Li et al, 2017). For example, alanine and glycine have a sweet taste, and glutamic acid has an umami taste (Prakash et al, 2015). Mo et al (2016) reported that the supplementation of (Lee et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…have been reported as the most common genera isolated from dried fish (Deng et al., 2021). In addition, the dominant species in dried salted TQF including A. niger , A. fumigatus and A. flavus have been reported in dried fish in India with a TFC of 5 × 10 3 CFU/g (Prakash et al., 2011). Aspergillus spp.…”
Section: Resultsmentioning
confidence: 99%
“…Other preservation methods reduce fish organoleptic scores. For example, heating technology causes the texture to become very tough and causes dehydration of fish muscle and shrinkage of fish filaments [ 65 ]. Smoking is a preservation method that provides heat and antimicrobial smoke chemicals to reduce the water activity in fish.…”
Section: Discussionmentioning
confidence: 99%